Application of the Grain-Based Rock-Eval Pyrolysis Method to Evaluate Hydrocarbon Generation, Expulsion, and Retention of Lacustrine Shale - Liao, Lingling; Wang, Yunpeng; Chen, Chengsheng; Pan, Yinhua (Frontiers in Earth Science, 2022)
The study on hydrocarbon generation, expulsion, and retention of shale is becoming more and more important as the exploration of unconventional oil and gas worldwide. There are multiple sets of lacustrine shales in the eastern area of China, which show a great potential for shale oil/gas exploration. In this study, a grain-based Rock-Eval pyrolysis method was conducted on three sets of lacustrine shales, including the Nenjiang shale, Shahejie shale, and Maoming oil shale, to evaluate the hydrocarbon generation, expulsion, and retention. For comparison, pyrolysis of kerogen from the three shale samples was also carried out under the same experimental conditions. The Maoming oil shale showed a slightly broader distribution of activation energies than the Nenjiang and Shahejie shales, while the Nenjiang shale showed higher dominant activation energy than the Shahejie shale and the Maoming oil shale. At laboratory heating rates (5–25°C/min), the corresponding temperature to the maximum hydrocarbon generating rate of shale grains was collectively higher than that of their kerogen, especially for the Nenjiang and Shahejie shales, which implies a lagging effect during the hydrocarbon generation and expulsion process for the shales. By calculating the differences in hydrocarbon yields between shale grain and kerogen samples, the content and proportion of the retained hydrocarbons were measured at different maturation stages. The results showed that the Nenjiang shale from the Songliao Basin has the strongest retention ability but the weakest expulsion ability, whereas the Shahejie shale from the Dongying Depression has the strongest expulsion ability but the weakest retention ability among the three samples. Moreover, it is found that the pore structure of lacustrine shales is likely the principal factor controlling the hydrocarbon retention ability/capacity. This study is expected to provide a geochemical quantitative basis for evaluating hydrocarbon generation, expulsion, and retention of shale.